(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2024)
Language has proven to be an important factor in film performance models, film finance considerations, and festival program selections. This essay uses multi-year global data sets (UN and supplementary databases) to analyse the relationship between the languages in which a film is produced and offered to cinemagoers on the one hand, and the co-production activities and dynamics which engender these patterns on the other hand. While European Commission policies, underlining the peculiar “linguistic polity”of the European Union, have been influential in the making of multilingual cinema productions motivated by subsidy rules, taxation and grant schemes, the pattern is rather global, reflecting uptake of cinematic product in many “territories” and the mobilization of film across national and regional language divides. The analysis shows that Europeanization has much wider implications beyond Europeans’ cultural consumption and identity construction, with Europe’s co-production policies casting a wider net of cultural resistance to Global Hollywood and its majority of English-language blockbusters as well as attending to language preservation in the European neighborhood in addition to Europe, where local and regional heritage policies are well instituted. The study examines the results against Abram de Swaan’s theory of the Global Language System, examining the Q-value theory to the language patterns emerging from film productions with multiple languages, which must be assessed in its relation to cultural consumption that may not follow from formal schooling and habitus formation.